Standar Waktu Pelayanan Truck Round Time dalam Meningkatkan Kinerja Receiving di PT. Terminal Peti Kemas Surabaya - Yunus, Abdul Rohman; Adi Purwanto Nugroho, F. X.; Pradana Putra A. S., Revian (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2022)
The aim of this study is to determine the standard truck round time (TRT) service time in improving receiving performance, identify the causes and impacts of TRT exceeding the standard set time. The research design used is descriptive research with a qualitative approach. Sources of data in this study are divided into primary data sources obtained from interviews, observations and literature studies and documentation of printed books, and journals . The result of this research is that the service quality at PT. Terminal Petikemas Surabaya is good because the dominant number of trucks on TRT is less than 30 minutes, although it can be indicated that there is a decrease in performance. This decline in performance is demonstrated by an increase in the number of trucks from 2019 to 2022 on TRT for more than 30 minutes. The causes of the TRT that exceeds the standard determination time are the density factor in the stacking field, the equipment factor, the human resource factor and the natural factor. The negative impact of TRT that exceeds the standard setting time is the disruption of loading and unloading activities, internal company losses and decreased customer loyalty. Suggestions that can be used in overcoming the TRT (Truck Round Time) problem are that good coordination is needed in accordance with Standard Operating Procedures (SOP), improvisation from both human resources, systems and equipment as well as yard planners carrying out various plan innovations by shortening slots so that RTG movements are not too displacement length.